Protecting the poor during adjustment in Latin America and the Caribbean in the 1980s. How adequate was the World Bank response?. Frances Stewart - International Development Centre, Centro Studi Luca d'Agliano (Italia); Stewart, Frances (Torino, Italia : International Development Centre, 1992)
El artículo analiza la incidencia de las políticas del Banco Mundial en la pobreza en cuanto al ajuste durante los ochentas
Keywords: AMERICA LATINA; ECONOMIA; POBREZA; DESARROLLO; AJUSTE ESTRUCTURAL